Desenvolvimento da microbiota oral de bebês: análise longitudinal por pirosequenciamento da microbiota de bebês e suas mães dentro de um Programa de Saúde Bucal para Primeira Infância - Sangalli, Jorgiana [UNESP] (2014)
Data on infants' oral microflora and how it changes in time is of utmost importance for the prevention, diagnosis and treatment of oral diseases in early stages. The goal of this study was evaluate, longitudinally, in the periods of 6, 12, 18 and 24 months of age, the oral microbiome of healthy babies and their mothers by pyrosequencing analysis. Seventy-four pairs of mothers/babies followed in a Program of Oral Healthy were included in the study. A total of fifty-eight participated in all the experimental period. The population of babies was followed during all the period, receiving orientation on oral health and procedures foreseen in the protocol of the referred program. Data on diet, oral hygiene, presence of teeth, prevalence of caries, and periodontal conditions of babies and their mothers were collected. For pyrosequencing analysis, 5 pairs of babies and mothers were selected following rigorous criteria of inclusion, in order to obtain a homogeneous sample of babies who did not develop caries during all the evaluation period. Also, samples from of the only baby who developed caries along the study were analyzed. Samples of saliva and dental biofilm from the babies and mothers were analyzed for the microbial diversity by pyrosequencing 454 of products of PCR of 16S ribosomal gene. The effectiveness of the Oral Health Program in this study was confirmed with the occurrence of caries in only 1 of the babies (1.51%) followed during 24 months. Salivary and biofilm microbial diversities of babies were stable in relation to the number of Phyla during the evaluation periods. A considerable increasing in the number of genus in babies' saliva was observed in the period of 6 to 12 months of age. After this period, the distribution was stable. At the age of 12 months, 77 different genus were found in the microbioma of infants' dental biofilm and this value was higher when compared to ...